SISTEM SPASIAL DAN TIPOLOGI RUMAH PANGGUNG DI DESA LOLOAN, JEMBRANA (BALI) - Dinar Sukma Pramesti (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2014)
Abstract Loloan is one of many unique villages located across the Jembrana Regency (Bali). Historically this community is descended from the Bugis ethnicity who sailed from Celebes Island to Bali. It is believed they were the first Muslim missionaries to spread Islamic beliefs on the island. Their arrival was acknowledged by the King of Jembrana who then provided them with land to settle. They populated this newly formed settlement with Bugis style's stilt houses, an unfamiliar form of home to the Balinese. The community has over time developed a distinctive living environment, extending the Bugis traditions. Given different resources as well as other natural circumstances compared to those found back home in Bugis, the Loloan community developed a range of stilt houses. The objective of this paper is to study the typology of stilt houses existing in this community, and the underlying factors determining their physical forms. The study was conducted using qualitative methods. The analysis was carried out by examining the spatial structure and architectural forms at both macro (settlement) and micro (houses) levels. Data collection was done by carrying out a literature study, interviews and physical observation. Research findings show there are four types of stilt houses in the Loloan community. Determining factors behind the emergence of this typology include socio cultural aspects, economic conditions, activities of the inhabitants, communal interactions taking place in the domestic sphere, building age, land availability and preferences of individuals living in the house. Key words: typhology, stilt house, spatial structure, house form AbstrakLoloan merupakan salah satu dari beragam komunitas unik yang ada di Kabupaten Jembrana. Secara historis, Komunitas Loloan berasal dari Bugis yang berlayar dari Pulau Sulawesi ke Bali. Mereka dipercaya sebagai penyebar Agama Islam pertama yang datang ke Bali. Raja Jembrana pada waktu itu menyambut kedatangan mereka dengan memberi sebuah area untuk bermukim di Loloan. Mereka membangun beragam rumah panggung gaya Bugis, sebuah struktur yang tidak lazim ada di beragam permukiman di Bali. Seiring waktu, komunitas Loloan memunculkan sebuah permukiman yang berbeda. Karena adanya perbedaan sumber daya pendukung dan kondisi hidup dibanding dengan yang mereka temukan di Bugis, masyarakat Loloan telah memunculkan beragam bentuk rumah panggung. Tujuan artikel ini adalah menstudi tipologi wujud rumah panggung di Loloan beserta faktor-faktor yang menentukan keberadaannya. Studi ini dilaksanakan dengan menggunakan pendekatan kualitatif. Analisa dilakukan terhadap struktur spasial dan bentuk arsitektur, baik yang ada di leval makro (permukiman) maupun mikro (rumah). Data pendukung diperoleh melalui studi literatur, wawancara dan observasi fisik. Temuan studi menunjukan bahwa terdapat empat tipe rumah panggung di Loloan. Adapun faktor-faktor yang melatarbelakangi kemunculan tipe rumah ini melingkup aspek sosial budaya, ekonomi, aktivitas penghuni, umur dan kondisi bangunan, interaksi komunal, ketersediaan lahan, dan preferensi individu yang tinggal di dalamnya. Kata kunci: tipologi, rumah panggung, struktur ruang, bentuk arsitektur